Analyzing Employee Perception of Good Governance in Municipal Governments by Using Structural Equation Modeling - Ali Oncu; Muhittin Tolga Ozsaglam; Fehiman Eminer (SAGE Open)
The understanding of good governance (GG), which was put into practice in the 1980s and gained global popularity rapidly, started to be discussed for Northern Cyprus (NC) in the 2000s. This research aims to analyze the implementation of GG principles and, the data was collected primarily from employees of the six municipalities of NC. GG as perceived by employees who are providers of local services and the factors that affect the perception of GG are analyzed with structural equation modeling. Findings indicate that there are differences in the perception of GG among the municipalities. Structural equation model shows that education and income level of employees has an impact on the perceived GG. This shows that financial status of the municipalities affects good governance indicators. As a result, it is important for the local governments to solve their financial problems while implementing good governance practices.